Electroactive Scaffolds to Improve Neural Stem Cell Therapy for Spinal Cord Injury - Mutepfa, Anthea R.; Hardy, John G.; Adams, Christopher F. (Frontiers in Medical Technology, 2022)
Spinal cord injury (SCI) is a serious condition caused by damage to the spinal cord through trauma or disease, often with permanent debilitating effects. Globally, the prevalence of SCI is estimated between 40 to 80 cases per million people per year. Patients with SCI can experience devastating health and socioeconomic consequences from paralysis, which is a loss of motor, sensory and autonomic nerve function below the level of the injury that often accompanies SCI. SCI carries a high mortality and increased risk of premature death due to secondary complications. The health, social and economic consequences of SCI are significant, and therefore elucidation of the complex molecular processes that occur in SCI and development of novel effective treatments is critical. Despite advances in medicine for the SCI patient such as surgery and anaesthesiology, imaging, rehabilitation and drug discovery, there have been no definitive findings towards complete functional neurologic recovery. However, the advent of neural stem cell therapy and the engineering of functionalized biomaterials to facilitate cell transplantation and promote regeneration of damaged spinal cord tissue presents a potential avenue to advance SCI research. This review will explore this emerging field and identify new lines of research.